Participatory crop improvement for intercropped maize on Bari land terraces with trees - Tiwari, T.P; Virk, Daljit S.; Sinclair, Fergus L. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Maize (Zea mays L.) is the most important crop in the middle hills of Nepal and is mostly grown in association with finger millet (Eleusino coracana Gaertn) and fodder trees. Seven maize varieties have been recommended for the hills but few farmers have adopted them. As a prerequisite to designing a participatory maize-improvement program for the middle hills that could reverse declining yields, local knowledge and practice were investigated and combined with micro-meteorological measurements at three sites, each with 20 participating farmers.